IDENTIFIKASI BIOTA PERAIRAN DILINDUNGI YANG TERTANGKAP (BYCATCH) DAN DIDARATKAN DI PELABUHAN PERIKANAN NUSANTARA BRONDONG, LAMONGAN, INDONESIA - Rizka Rahmana Putri; Hidayati Hidayati; Anita Wahyu Ningsih; Ariyani Dian Wahyu Savitri; Adyos Bobby Chandra; Fitria Hersiana Afifa; Rachmad Azmi Fatahillah (Universitas Mataram, 2026)
Indonesia is a country with exceptionally high biodiversity and endemism. However, this condition also increases the risk of overfishing, which can lead to population declines and even species scarcity. In practice, fishing activities often capture non-target organisms (bycatch), including marine species with important conservation status listed in the International Union for Conservation of Nature (IUCN) Red List and the appendices of the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES). Therefore, conservation efforts for sharks and rays are crucial due to high fishing pressure, including bycatch, as well as their low reproductive rates, which make them particularly vulnerable to extinction. The use of non-selective fishing gear further increases the likelihood of accidental capture, highlighting the need for sustainable fisheries management, fisher education, and bycatch reduction measures. This study focuses on protected aquatic biota to obtain data on sharks and rays landed at the Brondong Nusantara Fishing Port. Data were collected through direct observation of protected species landed at the port. The results show that several species are listed under CITES Appendix II, including Rhynchobatus springeri, Sphyrna zygaena, Carcharhinus dussumieri, Carcharhinus melanopterus, Carcharhinus limbatus, and Rhina ancylostoma. Additionally, several species are included in the IUCN Red List, such as Telatrygon zugei, Ginglymostoma cirratum, Galeocerdo cuvier, Dasyatis zugei, Chiloscyllium punctatum, Himantura uarnak, Mustelus manazo, Aetobatus ocellatus, and Chiloscyllium plagiosum. This identification and documentation are essential for determining conservation status and supporting policies aimed at balancing utilization and conservation of shark and ray resources in Indonesia.